Mini Review; Differentiation of Human Pluripotent Stem Cells into Oocytes - Wang, Gaifang; Farzaneh, Maryam (Current Stem Cell Research & Therapy, 2020)
Primary Ovarian Insufficiency (POI) is one of the main diseases causing female infertility that occurs in about 1% of women between 30-40 years of age. There are few effective methods for the treatment of women with POI. In the past few years, stem cell-based therapy as one of the most highly investigated new therapies has emerged as a promising strategy for the treatment of POI. Human pluripotent stem cells (hPSCs) can self-renew indefinitely and differentiate into any type of cell. Human Embryonic Stem Cells (hESCs) as a type of pluripotent stem cells are the most powerful candidate for the treatment of POI. Human-induced Pluripotent Stem Cells (hiPSCs) are derived from adult somatic cells by the treatment with exogenous defined factors to create an embryonic-like pluripotent state. Both hiPSCs and hESCs can proliferate and give rise to ectodermal, mesodermal, endodermal, and germ cell lineages. After ovarian stimulation, the number of available oocytes is limited and the yield of total oocytes with high quality is low. Therefore, a robust and reproducible in-vitro culture system that supports the differentiation of human oocytes from PSCs is necessary. Very few studies have focused on the derivation of oocyte-like cells from hiPSCs and the details of hPSCs differentiation into oocytes have not been fully investigated. Therefore, in this review, we focus on the differentiation potential of hPSCs into human oocyte-like cells.
Keywords: differentiation